2020
DOI: 10.3390/infrastructures5060049
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Structural Health Monitoring Method for Reinforced Concrete Bridge Decks Using Ultrasonic Guided Waves

Abstract: This article presents the latest improvements in a recently developed nondestructive testing (NDT) approach for early detection of various flaws (corrosion, delamination, and concrete cracking) in reinforced concrete (RC) bridge decks. The proposed method involves the use of internal steel reinforcement as a wave guide for transmitting ultrasonic waves through the system and the measurement of leaked energy from the surface of the concrete. This paper builds upon the progress made in the previously published p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…UGWL has the ability to identify the onset and progression of flaws in RC structures such as concrete-rebar delamination, corrosion, and cracking. The team's previous work successfully demonstrated that UGWL is capable of identifying delaminations as small as 0.2 mm (0.008 in) and the onset of rebar corrosion [1][2][3]. A study conducted by Garcia et al [2] successfully demonstrated that the amplitude of the leaked energy that radiates from the reinforcing bar waveguide is sensitive to corrosion initiation and cracks.…”
Section: Ultrasonic Guided Wave Leakage (Ugwl) Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…UGWL has the ability to identify the onset and progression of flaws in RC structures such as concrete-rebar delamination, corrosion, and cracking. The team's previous work successfully demonstrated that UGWL is capable of identifying delaminations as small as 0.2 mm (0.008 in) and the onset of rebar corrosion [1][2][3]. A study conducted by Garcia et al [2] successfully demonstrated that the amplitude of the leaked energy that radiates from the reinforcing bar waveguide is sensitive to corrosion initiation and cracks.…”
Section: Ultrasonic Guided Wave Leakage (Ugwl) Methodsmentioning
confidence: 99%
“…While a range of ultrasonic frequencies (20-100 kHz) have been used in homogeneous concrete systems, 54 kHz was found to be optimal for this application [1]. Most ultrasonic guided wave studies on RC structures have utilized lower ultrasonic frequencies [1][2][3]27,29,30], mostly because the lower frequencies have a higher sensitivity to bond conditions and are easier to solve [27]. Since the concrete is a heterogeneous material, many agree that it is better to use lower frequencies in ultrasonic testing, typically 20 to 100 kHz [27].…”
Section: Ultrasonic Guided Wave Leakage (Ugwl) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concrete detector for rebar localization, depth measurement, and size estimation are necessary for the proper estimation of steel reinforcements in the existing old concrete bridge. New technologies, methods, and systems are still developed for the detection of steel rebars in concrete structures [ 61 , 62 , 63 , 64 ].…”
Section: Structural Analysismentioning
confidence: 99%